PERSEPSI MASYARAKAT DESA AKE JAWI TERHADAP KEBERADAAN TAMAN NASIONAL AKETAJAWE LOLOBATA (TNAL) KABUPATEN HALMAHERA TIMUR - Siti Murniati; Risky Nuri Amelia (JPG (Jurnal Penelitian Geografi), 2022)
Before it was made into the Aketajawe Lolobata National Park, the forest was a forest that was used by local people to meet their needs and survival in farming. Communities inside and outside can not be separated from the National Park area because in reality these communities have first lived in the area around the forest. This research was conducted with the aim to find out the perception of the Ake Jawi Village Community on the Existence of Aketajawe Lolobata National Park (TNAL). This study used descriptive qualitative method. The data used are primary data and secondary data. The data source is 22 families that directly border TNAL. Data collection techniques are observation and interviews. Respondents were selected by purposive sampling. Data analysis techniques using descriptive qualitative (data collection, data reduction, data display, verification / drawing conclusions).Based on data analysis, namely (1) Perception of a small percentage of people who have a good perception of the existence of a national park that the community considers that TNAL has a positive impact. It is hoped that the existence of a national park will continue to benefit from forest resources and maintain its sustainability for the foreseeable future. The public perception is not good, namely the presence of TNAL, does not provide anything but only reduces the area of their arable land that enters the TNAL area, which makes the community disturbed by the presence of TNAL. This is the case of many Ake Jawi Village respondents who have received elementary and secondary education. (2) The perception of the people of Ake Jawi Village is caused by external factors, namely the low level of education, lack of participation in socialization, lack of experience and lack of community knowledge about national parks and functions for the next life.